2014
DOI: 10.1177/1742715014543578
|View full text |Cite
|
Sign up to set email alerts
|

Distributing leadership across people and objects in a collaborative research project

Abstract: This paper examines how distributed leadership involving actor-object couplings may contribute to coordinated action across disparate thought worlds. We draw on ideas from French pragmatist sociology and on a case study of a successful collaborative research project involving participants from academia, government and practice settings to show how various kinds of objects (including material artifacts, more abstract concepts and human-material assemblages such as committees and procedures) come to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…We asked each respondent to represent the experiences of their organisation. Our sampling approach is consistent with other research employing expert elicitation, network and participatory approaches (e.g., Cohen et al 2012;Game et al 2013) and it aligns with methodological approaches in leadership studies (e.g., Mailhot et al 2016) The face-to-face expert interview involved a participatory network mapping activity to map leadership influences on the respondents' organizations. First we asked respondents to identify "Who and what provides leadership in the work that your organisation does (e.g., activities on the ground, policies your organisation develops, research your organisation undertakes, etc.)…”
Section: Data Collectionmentioning
confidence: 63%
See 2 more Smart Citations
“…We asked each respondent to represent the experiences of their organisation. Our sampling approach is consistent with other research employing expert elicitation, network and participatory approaches (e.g., Cohen et al 2012;Game et al 2013) and it aligns with methodological approaches in leadership studies (e.g., Mailhot et al 2016) The face-to-face expert interview involved a participatory network mapping activity to map leadership influences on the respondents' organizations. First we asked respondents to identify "Who and what provides leadership in the work that your organisation does (e.g., activities on the ground, policies your organisation develops, research your organisation undertakes, etc.)…”
Section: Data Collectionmentioning
confidence: 63%
“…Our approach follows an emerging stream of research in leadership studies on the role of people and objects/artefacts in distributed leadership (Spillane et al 2004;Bryson et al 2009;Oborn et al 2013;Mailhot et al 2016). Some scholars analyse how human agents employ objects (i.e., concepts, committees or technologies) to achieve outcomes through their leadership practice (Mailhot et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case study Mailhot, Gagnon, Langley, and Binette, (2016); Barnes et al (2002Barnes et al ( , 2006, conducing a multi-case study, identified some success factors and organized them into categories (see Figure 2.8). Barnes et al (2006) argue that while research on university-industry collaboration has concentrated primarily on the "cultural gaps", they confirm previous research that suggested the existence of an overlap between management factors affecting the success in both industry-industry and university-industry relationships (recent research emphasizes that a contingent approach to the type of partner should be considered -this will also be discussed in this section).…”
Section: Leadershipmentioning
confidence: 99%
“…Bearing this in mind, a clear and common agreed definition of objectives, responsibilities and the whole project setup has been shown to have "a positive influence on the involvement and commitment of partners within a collaborative project" (Barnes et al, 2002, p. 399). Morandi 2013 Going forward through understanding the "black box" of collaborative R&D projects, Mailhot et al, (2016) focused on the leadership issue, but going beyond the human factor. While most studies in collaborative R&D project management focus on planning issues to guarantee a shared vision, they observed how "various kinds of objects (including material artefacts, more abstract concepts and human-material assemblages such as committees and procedures) came to participate in and contribute to the practices of individual leaders, connecting different worlds, and enabling the enactment of leadership roles" (Mailhot et al, 2016, p. 55).…”
Section: Figure 28: the Good Practice Model Incorporating Universitymentioning
confidence: 99%